2014
DOI: 10.5120/18131-9251
|View full text |Cite
|
Sign up to set email alerts
|

A New Morphology-based Method for Text Detection in Image and Video

Abstract: Text supply crucial suggestions for understanding video content, also the information that the text convey is much more concise than corresponding audio or video. The reason is that we need language knowledge to understand the text, and the knowledge itself does not need to be embedded in the text data. Text streams contain very rich semantic information. How to effectively extract information from text is an important component in video content analysis and semantics research. In this paper, a new morphology-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…In order to determine whether the found part contains text or not, an algorithm was developed to check the structure of the part. [17]. In a similar study, text regions of document images are identified based on the differences between opening and closing operations [18].…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…In order to determine whether the found part contains text or not, an algorithm was developed to check the structure of the part. [17]. In a similar study, text regions of document images are identified based on the differences between opening and closing operations [18].…”
Section: Literature Reviewmentioning
confidence: 99%
“…• The area of the region must be of a specific size to eliminate small contours in the invoice. • The aspect ratio, width, and height of the region must be within a certain range for it to be accepted as text or a table [17], [36]. • Within the bounding box of the image shown in Fig.…”
Section: ) Table and Text Detection With Image Processingmentioning
confidence: 99%
“…VS is being used in security surveillance systems to detect and analyze suspicious or anomalous activities. Personal VS is used to share occasional videos on social media, generate sports highlights, make trailers of movies and serials and video content indexing to facilitate fast browsing of huge video through a video search engine, and so on [16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%